Zirconium Oxide and Iron Zirconate Obtained from Citrus Pectin and Nitrates Applied in the Photo-fenton-like Process - Cristiane Antoniazzi; Eryza Guimarães de Castro; Fauze Jacó Anaissi (Orbital: The Electronic Journal of Chemistry, 2018)
This paper describes the synthesis and characterization of zirconium oxide (ZrO2) and of the mixed oxide of iron (iron zirconate), obtained by gelification (80 °C) and calcination (600 °C) of citrus pectin and inorganic nitrates. Thermal analysis demonstrated the presence of organic matter in the solid after calcination, indicating that pectin was strongly coordinated to the oxide phases. The X-ray diffractogram for zirconate, do not show peaks associated with the iron oxides phases, indicating that the zirconia matrix remained unchanged. Electronic spectra supported observations concerning the color of the solids, with bands assigned to d–d transitions of the iron ions. Both Raman spectra and X-ray diffractogram indicated the presence of the tetragonal phase of ZrO2, and scanning electron microscopy images showed that the solids had similar and particulate morphologies. Finally, the test for dye degradation using iron zirconate proved efficient, with a degradation index greater than 90.3% after 60 min.